1992
DOI: 10.1080/02701367.1992.10607573
|View full text |Cite
|
Sign up to set email alerts
|

A Biomechanical Analysis of Four Sprint Start Positions

Abstract: The sprint starts of 12 skilled collegiate sprinter/hurdlers were filmed for four different sprint start conditions. Ground reaction forces were collected for the first step out of the blocks and velocities through a 2-m speed trap immediately following the first support phase were recorded. The subjects employed their preferred right-left leg placement in the blocks, while the anterior-posterior spacing of the front block with respect to the starting line and the amount of forward lean in the set position wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
70
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 17 publications
3
70
0
2
Order By: Relevance
“…It is seen that different sprint start positions were suggested in each different study (5,16,27,28,41). These studies were conducted on highly different study samples (male, female, young, adult, amateur, elite athletes), accordingly results of the studies showed variations depending on the biomechanical, morphological and anthropometric characteristics of these athletes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is seen that different sprint start positions were suggested in each different study (5,16,27,28,41). These studies were conducted on highly different study samples (male, female, young, adult, amateur, elite athletes), accordingly results of the studies showed variations depending on the biomechanical, morphological and anthropometric characteristics of these athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, maximal and mean horizontal propulsive force generation capacities are said to be the main factor that seperates talented athletes from others (7). Therefore, ideal sprint start position that leads to maximal and mean propulsive forces should be assessed precisely considering inter-individual differences since this position is greatly affected by anthropometric measures of athletes (8,41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations